THE IMPLEMENTATION OF GOVERNMENT AUTHORITY IN RELATION TO THE SPORTS POLICY OF MALUKU PROVINCE GOVERNMENT - Albertus Fenanlampir; Rahmat Hidayat (Faculty of Teacher Training and Educational Sciences, Pattimura University Indonesia, 2020)
The development of sports in Maluku in its implementation is always based on Law Number 3 of 2005 concerning the National Sports System, that